2019
DOI: 10.15244/pjoes/101621
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potential of Fast-Growing Energy Plants: Challenges and Perspectives – a Review

Abstract: Contamination of soil by toxic elements is a global issue of growing importance due to the increased anthropogenic impact on the natural environment. Conventional methods of soil decontamination possess disadvantages in forms of environmental and financial burdens. This fact leads to the search for alternative approaches of remediation of contaminated sites. One such approach includes phytoremediation. Phytoremediation advantages consist of low costs and small environmental impact. Several fast-growing energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 104 publications
(141 reference statements)
0
19
0
Order By: Relevance
“…Soil contamination can damage and cause deterioration of water quality and have a negative impact on the environment [24][25][26]. Many studies have found that land-use change [27], cultivated plants, surrounding transport networks and hydrology of the territory [28,29], diversity of land use [30], and different ways of maintaining the soil are related to soil contamination [27][28][29][30][31][32][33].…”
Section: Heavy Metals In Soil-plant Systemsmentioning
confidence: 99%
“…Soil contamination can damage and cause deterioration of water quality and have a negative impact on the environment [24][25][26]. Many studies have found that land-use change [27], cultivated plants, surrounding transport networks and hydrology of the territory [28,29], diversity of land use [30], and different ways of maintaining the soil are related to soil contamination [27][28][29][30][31][32][33].…”
Section: Heavy Metals In Soil-plant Systemsmentioning
confidence: 99%
“…Heavy metal pollution caused by human facilities is a global problem in both terrestrial and aquatic environments systems [1][2]. The release of large amounts of hazardous waste, heavy metals and pollutants into the environment by mining, agriculture, textile, industrial and human activities causes pollution on the ecosystem [1,[3][4]. Phytoremediation is a new technology that uses plants to clean-up polluted environments [1,[5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of suitable plants for remediation is an important factor for solving the heavy metal pollution. These contaminated areas can be remediated by plants that accumulate heavy metal in their aerial parts [1,3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large fragmentation of land ownership negatively affects the land market and restricts the sale of agricultural land, which in turn increases land rent [26]. It leads to the creation of large production blocks and consequently to the homogenization of land use, with a negative impact on sustainable land use and biodiversity [27,28]. Moreover, the minimum size of land stipulated by law has led to increased co-ownership of land [29].…”
Section: Introductionmentioning
confidence: 99%